Perlindungan Hukum bagi Awak Kabin dalam Perjanjian Waktu Tertentu (PKWT) PT Garuda Indonesia - Anastasia; Ida Ayu Putu Widiati; A. A. Sagung Laksmi Dewi (Warmadewa Press, 2021)
The existence of cabin crew is very much needed in a flight to serve airplane passengers, including Garuda Indonesia as one of the state-owned airlines that tries to provide flight safety in the field of air transportation. This study aims to determine the implementation of the Specific Time Work Agreement on the cabin crew of Garuda Indonesia homebase Denpasar and to find out the legal protection for flight attendants in the Fixed Time Work Agreement on the cabin crew of Garuda Indonesia homebase Denpasar. This type of research is empirical research. Empirical research is carried out on the real situation in the community or the surrounding environment with the aim of finding facts or existing legal problems. The results showed that the implementation of the Fixed Time Work Agreement on the cabin crew of PT Garuda Indonesia homebase Denpasar is closely related to employment between workers and companies. Fixed Term Work Agreement at PT Garuda Indonesia is regulated in Company Regulations. In general, the protection of workers has been regulated in Law No. 13 of 2003 concerning Manpower. The attitude of open wages to cabin crew will definitely have a positive impact on the welfare of employees in the morning.